Study on Ocular Prosthesis for the Rehabilitation Of Patient With Ex-ophthalmic Socket (Journal of Chittagong Medical College Teachers' Association, 2020)
Background : Among the extra-oral maxillo-facial prosthesis, single ocular prosthesis is one of the important type- which is concerned with the patient’s psychological, emotional status and facial expression. This prosthesis fits over an orbital implant and under the eye-lids. Typically known as glass eye which provides no vision only aesthetics. Ocular prosthesis are made of glass, medical grade plastics, PMMA, silicone, plaster. Ocular prosthesis may be ready-made or custommade. The objective of the study was to compare the ready-made and custom-made ocular prosthesis for providing best rehabilitation of patient with ex-ophthalmic socked (Single).Materials and methods: It was a prospective comparative in vivo study carried out Department of Prosthodontics, Faculty of Dentistry, BSMMU, Dhaka from January 2009 to December 2010. 40 patients with single ex-ophthalmic socket were selected from outpatient department considering the inclusion and exclusion criteria. The patients were divided into two groups. In group A 20 patients were given custom-made ocular prosthesis. In group B 20 patients were given ready-made ocular prosthesis, patients were observed clinically and evaluation were done on the day of insertion, after 1 week, 2 week, 1 month, 3 months, 6 months interval.Results: The results were evaluated by specific parameter as comfort, aesthetic, movement of the ocular prosthesis during facial expression. After observing the patients it was revealed that custom made ocular prosthesis was better in comfort, aesthetic and movement during facial expression than readymade one.Conclusion : This study revealed that custom made ocular prosthesis is better for the rehabilitation of the patient with single ex-ophthalmic socket. Ready made one can be used for a short period of time as a temporary measure.JCMCTA 2019 ; 30 (2) : 52-56